Determinants and impact of early marriage on mother and her newborn in an urban area of Davangere: a cross-sectional study - Sandhu, Navneet Kaur; R. G., Geethalakshmi (International Journal Of Community Medicine And Public Health, 2017)
Background: Early marriage is a long established custom in India. In spite of the legislations prohibiting early marriages, the prevalence of child marriages in our country is 30.2%, with the highest prevalence in Rajasthan (35.4%) and lowest in Himachal Pradesh (0.5%).Thus, this study was undertaken to study the prevalence, determinants and impact of early marriage on the mother and her newborn in an urban area of Davangere. Methods: A cross-sectional study was conducted over a period of 6 months in the Urban Family Welfare Centre, Doddapete. A total of 900 mothers were interviewed with the help of pre- designed and semi-structured questionnaire after taking informed consent. Results: The prevalence of child marriage in the present study was found to be 13% with 81% mothers belonging to lower socio- economic status and 77% belonging to Muslim religion. Most (62%) mothers married before the age of 18 years due to economic reasons. 54% of the mothers who married before the age of 18 years faced complications during delivery. 6% of the mothers married before the age of 18 years gave birth to low birth weight babies. Conclusions: The literacy and socio-economic status of the mother and her parents was observed as a major determinant in deciding the age at marriage. In spite of the prevailing religious traditions and socio-cultural influences that promote child marriage, an attempt should be made to educate the community regarding the medical and legal aspects of early marriage.